2007
DOI: 10.1002/cphc.200600624
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Exchange Processes on Solvated Lithium Cations: DMSO and Water/DMSO Mixtures

Abstract: Solutions of LiClO(4) in solvent mixtures consisting of dimethylsulfoxide (DMSO) and water, or DMSO and gamma-butyrolactone, were studied by (7)Li NMR spectroscopy (for complexation by cryptands in gamma-butyrolactone as a solvent, see: E. Pasgreta, R. Puchta, M. Galle, N. J. R. van Eikema Hommes, A. Zahl, R. van Eldik, J. Incl. Phen., 2007, 58, 81-88). Chemical shifts indicate that the Li(+) ion is coordinated by four DMSO molecules. In the binary solvent mixture of water and DMSO, no selective solvation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…Following the suggestions of Hartmann et al, [13] and for comparison with recent studies on solvent exchange at Li + , [17,18,22] Be 2+ , [19,23] and Al 3+ , [20,21] we fully optimized the structures at the B3LYP/6-311+G** level of theory [24] and characterized by computation of vibration frequencies the structures as local minima or transition states.…”
Section: Quantum Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the suggestions of Hartmann et al, [13] and for comparison with recent studies on solvent exchange at Li + , [17,18,22] Be 2+ , [19,23] and Al 3+ , [20,21] we fully optimized the structures at the B3LYP/6-311+G** level of theory [24] and characterized by computation of vibration frequencies the structures as local minima or transition states.…”
Section: Quantum Chemical Methodsmentioning
confidence: 99%
“…15 , M = Li (m = 4, n = 1), [22] Be (m = 4, n = 2), [23a] Zn (m = 6, n = 2) and Al (m = 6, n = 3) [21] complexes versus the charge on the metal ion. [21] shows that the sum of the metal-nitrogen bond lengths (∑(M-NCH)) as a quantum [21].…”
Section: +mentioning
confidence: 99%
“…Larger aggregates are most frequently monosolvated or disolvated depending on the size of the solvent (and solute), but lithium is generally considered to be tetracoordinated [36,39]. Solvent exchange between the coordinating solvent and the solvent in the bulk and flexibility due to hemilabile ligands are also processes that may take place, and these are dynamical temperature-and concentration-dependent processes, phenomena well studied by both NMR and computational techniques [28,[48][49][50][51][52][53][54][55]. Solvation energies of lithium organic compounds are routinely estimated computationally and have been compared with experimental results in several studies.…”
Section: Solvation Effectsmentioning
confidence: 99%
“…The kinetics of the ligand exchange process between solvated lithium ions (solvated by g-butyrolactone, (S), an industrially pertinent solvent) and lithium ions complexed with the cryptands, C222 or C221, (L), have been studied by 7 Li NMR spectroscopy. 380 Analysis from earlier studies using other solvents indicated that the reaction follows two competing mechanisms, bimolecular association (between Li (L) þ and Li(S) þ ) and unimolecular reaction involving Li(L) þ . The former process would be expected to proceed by an associative mechanism and when S ¼ gbutyrolactone, the present study yields an entropy of activation of a value that supports an associative interchange mechanism, although the rate of this reaction exhibited almost no dependence upon pressure.…”
Section: Main Group Elementsmentioning
confidence: 99%
“…This study confirmed that experimental and theoretical evidence supports a coordination number of four for both DMSO and DMSO/water mixtures. 386 A computational study suggested that ligand exchange on [Li(DMSO) 4 ] þ follows a limiting associative (A) mechanism, whereas displacement of coordinated water by DMSO follows an associative interchange (I a ) mechanism. A similar investigation indicated that Li þ ions in acetonitrile exhibit four-coordination and that in a binary aqueous acetonitrile mixture, the more strongly coordinating water leads immediately to formation of [Li (H 2 O) 4 ] þ .…”
Section: Main Group Elementsmentioning
confidence: 99%